Penggunaan Metafora dalam Lirik Lagu Album 最偉大的作品 Karya 周杰倫 (Jay Chou) melalui Pendekatan Teori Semantik Stephen Ullmann - Khalid Ilham Mawardi; Subandi Subandi (Journal of Creative Student Research, 2026)
Metaphor is a figurative language device in linguistic studies used to convey meaning indirectly through comparison or similarity between two different entities, producing more imaginative and expressive meanings. According to Stephen Ullmann, metaphor is defined as a transfer of meaning from one object to another based on perceived similarity, which enables abstract concepts to be expressed through more concrete representations. This study aims to describe the types of metaphors and explain their metaphorical meanings in Jay Chou’s album Zuì Wěidà de Zuòpǐn, based on Ullmann’s semantic theory. This research uses a qualitative descriptive approach with data taken from song lyrics in the album. Data collection was conducted through documentation techniques involving identification, transcription, and classification of metaphorical expressions. The findings reveal eighteen metaphorical data consisting of four anthropomorphic metaphors, three animal metaphors, eight concrete-to-abstract metaphors, and three synesthetic metaphors. The most dominant type is the concrete-to-abstract metaphor, which is widely used to express emotional experiences such as love, loss, hope, and loneliness through visual symbols and natural elements. The metaphorical meanings identified reflect human emotional experiences, including nostalgia, longing, life reflection, and hope expressed in a poetic and imaginative form. Thus, metaphor functions not only as an aesthetic linguistic device but also as an artistic means of conveying deep emotional and conceptual meanings in song lyrics.